A comparative study of the damping oscillation function of TCSC and UPFC - Furini, M. A. [UNESP] (2008)
The main objective of this work is to analyze the ability of FACTS devices like TCSC and UPFC to damp low frequency oscillations and a POD controller is also included. A comparative study of damping effect of those devices IS carried out. The Power Sensitivity Model (PSM) is used to the representation of the electric power system. Sensibility analysis using the residue method shows the best place for the installation of FACTS and the procedure to determine POD parameters. ©2008 IEEE.